Structure and Wear Resistance of NV Composite Layer on Automobile Stainless Steel - ZHANG Ya - biao, LI Yong - feng, LI Ming (Cailiao Baohu)
In order to improve the surface quality of 316L stainless steel for vehicles, the powder vanadizing and the salt bath nitriding technology were used to prepare the coatings of single powder vanadizing, powder vanadizing followed by nitriding(N/V), and nitriding followed by powder vanadizing(V/N) on the surface of 316L stainless steel. The microstructure and wear resistance were analyzed by SEM, EDS, XRD, hardness tester and friction tester. Results showed that compared with single V coating, NV coating had a smoother surface, mainly containing NV(111) and α - Fe. The V/N coating had a high content of N element, and a large amount of Fe was formed on the surface of the coating. The hardness of the V/N coating (1 691 HV) was higher than that of the N/V coating (1 546 HV). The hardness of V/N and N/V coatings was higher than that of single vanadium coating. The hardness of the coatings were much higher than that of the 316L stainless steel substrate. Compared with other coatings, the V/N coating had a smaller friction coefficient, only 0.26, which could quickly form a stable wear state, and forming a relatively gentle friction coefficient change curve. V/N coating was closely bound to the substrate and the depth of the wear scar is low, which avoided the generation of furrow.